Kondisi Pertumbuhan Masyarakat Desa Sidorejo Kabupaten Mojokerto Dalam Pencatatan Badan Pusat Statistik : Pertumbuhan Penduduk - Hikmah Muhaimin; Avrilia Angel; Nadia Ayu Amalia; Latifatul Annas; Raffelino Syahadatan Ramadani (Bahasa Indonesia, 2022)
The Central Bureau of Statistics (BPS) is a non-departmental government agency that functions as a provider of basic statistical data for the government and the general public, nationally and regionally. In terms of its structure, the Central Statistics Agency (BPS) is directly under the President. The Central Bureau of Statistics (BPS) is divided into three levels, Central BPS, Provincial BPS, and Regency/City BPS. This research uses a qualitative descriptive method. In the use of qualitative descriptive research methods the research describes in full and detail the state of the object to be studied (Sugiono, 2013). Data collection techniques using probability sampling. Included in Sampling Probability are simple random sampling, systematic sampling, stratified sampling and cluster sampling. After conducting interviews through population census data collection for sampling. The interview can be carried out through document research carried out. In researching this document, the researcher used a document provided by the Mojokerto Regency Central Statistics Agency called the REGSOSEK-K Document or the Questionnaire Socio-Economic Registration document through the interview method. 2022 shows that the condition of community growth in Sidorejo Village has decreased. This is caused by several factors including: 1. Migration of population, 2. Migration of households, 3. Death.